2012
DOI: 10.1111/j.1523-5378.2012.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact Long‐Type dupA as a Marker for Gastroduodenal Diseases in Okinawan Subpopulation, Japan

Abstract: Background Helicobacter pylori dupA can be divided into two types according to the presence or absence of the mutation. In addition, full-sequenced data revealed that dupA has two types with different lengths depend on the presence of approximately 600 bp in the putative 5' region (presence; long-type and absence; short-type), which has not been taken into account in previous studies. Methods A total of 319 strains isolated from Okinawa, the south islands of Japan, were included. The status of dupA and cagA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…The presence of dupA was 38.6 % in this study, which was relatively lower than that reported in South America and US (79.2 and 69.2 %) [8]. Intriguing, dupA in the region revealed an ORF of 2499-bp, which was a kind of conserved, intact and long-type dupA as recently reported [15,17]. Meanwhile, the long-type dupA is confirmed to produce the encoded protein in the study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The presence of dupA was 38.6 % in this study, which was relatively lower than that reported in South America and US (79.2 and 69.2 %) [8]. Intriguing, dupA in the region revealed an ORF of 2499-bp, which was a kind of conserved, intact and long-type dupA as recently reported [15,17]. Meanwhile, the long-type dupA is confirmed to produce the encoded protein in the study.…”
Section: Discussioncontrasting
confidence: 55%
“…Notably, as one base pair insertion (T or C) appears after the position 1385 in jhp0917 gene, a continuous ORF ''dupA'' was came into being in some clinical H. pylori strains. dupA was polymorphic [7,13], and the intact long-type dupA was reported, which had a longer open reading frame (2499 bp) than that of strain J99 and is a real virulence marker for severe outcomes in Okinawa, Japan [15]. Recently, our research found that most H. pylori strains had the more active East Asian-type cagA, intact cag PAI, virulent vacA genotypes in a littoral region of Northeast China at high risk of gastroduodenal diseases.…”
Section: Introductionmentioning
confidence: 95%
“…This may be due the bifurcated nature of its phylogeny and warrants further investigation. More recently, the presence of its adjacent vir genes has been recognized as a more reliable virulence marker in H. pylori (36,72,73). Evidence that the intact dupA cluster was found in a less virulent strain with cagPAI absent and vacA a putative pseudogene has suggested that the particular dupA cluster found in these strains could be a candidate marker for the prediction of related clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest dupA genotypes can also be defined as long type and short types in relation to location of the signal sequence of the N-terminal region. In Okinawa, only the long-type dupA was significantly associated with severe gastroduodenal diseases [79]. It remains unclear whether the short-type dupA produces a functional protein, or even whether long-type dupA without frame shift mutations are functional.…”
Section: Dupamentioning
confidence: 99%